2002
DOI: 10.1002/polb.10285
|View full text |Cite
|
Sign up to set email alerts
|

Relating fracture energy to entanglements at partially miscible polymer interfaces

Abstract: A new model has been developed to calculate the areal chain density of entanglements (⌺ eff ) at partially miscible polymer-polymer interfaces. The model for ⌺ eff is based on a stochastic approach that considers the miscibility of the system. The values agree between ⌺ eff calculated from the model and literature values for the reinforced interfaces. Using ⌺ eff calculated from the model, the interfacial width, and the average distance between entanglements, an equation for the fracture energy of nonreinforce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…This communication focuses on the effect of polydispersity on the phase behavior of polymer blends. It is well known that the phase behavior affects interfacial characteristics, such as the interfacial width30 and fracture energy30–32. Therefore, these results are relevant to studies on the effect of polydispersity on interfacial behavior.…”
Section: Resultsmentioning
confidence: 95%
“…This communication focuses on the effect of polydispersity on the phase behavior of polymer blends. It is well known that the phase behavior affects interfacial characteristics, such as the interfacial width30 and fracture energy30–32. Therefore, these results are relevant to studies on the effect of polydispersity on interfacial behavior.…”
Section: Resultsmentioning
confidence: 95%
“…Figure 10 plots the interfacial width as a function of the fracture energy. Previous work1, 9, 11, 32 has shown that a linear relationship exists between the fracture energy and the square of the interfacial width for amorphous polymer interfaces. Our data indicate that semicrystalline polymer interfaces do not show the same quantitative relationship between G c and w but clearly do show that G c increases with w .…”
Section: Resultsmentioning
confidence: 90%
“…For polymers, the diffusion process can be interpreted as the entanglements of polymer chains from different materials. [17][18][19] By controlling the annealing temperature and time, different interfacial thicknesses in the range of 5 to 50 nm can be generated. The temperature range of interest, where significant variation in the interfacial width is expected, falls between the melting temperatures of iPP and PE.…”
Section: Methodsmentioning
confidence: 99%